Simulations of liquid crystals in Poiseuille flow - Denniston, C; Orlandini, E; Yeomans, J (2001)
Lattice Boltzmann simulations are used to explore the behavior of liquid crystals subject to Poiseuille flow. In the nematic regime at low shear rates we find two possible steady-state configurations of the director field. The selected state depends on both the shear rate and the history of the sample. For both director configurations there is clear evidence of shear thinning, a decrease in the viscosity with increasing shear rate. Moreover, at very high shear rates or when the order parameter is large, the system transforms to a 'log-rolling state' with boundary layers that may exhibit oscillatory behavior. (C) 2001 Elsevier Science Ltd. All rights reserved.